Clinical Follow-up on Sagittal Fracture at the Temporal Root of the Zygomatic Arch: Does It Need Open Reduction? - Cheon, Ji Seon; Seo, Bin Na; Yang, Jeong Yeol; Son, Kyung Min (Archives of Plastic Surgery, 2013)
Background The zygoma is a major portion of the midfacial contour. When deformity occurs in this area, a reduction should be conducted to correct it. If a sagittal fracture at the temporal root of the zygomatic arch occurs, this also requires reduction, but it is difficult to approach due to its anatomical location, and the possibility of fixation is also limited. Thus, the authors attempted the reduction of sagittal fracture by two- or three-point fixation and the Gillies approach without direct manipulation. The preoperative and postoperative results of the patients were evaluated. Follow-up was performed to establish a treatment guideline.Methods A retrospective study was done with 40 patients who had sagittal fractures at the temporal root of the zygomatic arch from March 2009 to June 2012. Only two- or three-point fixation was performed for the accompanying zygomatic-orbital-maxillary fracture. The Gillies approach was used for complex fractures of the zygomatic arch, while the temporal root of the zygomatic arch was only observed without reduction. Preoperative and postoperative computed tomography and X-ray scans were performed to examine the results.Results The result of the paired t-test on preoperative and postoperative bone gap differences, the depression level, and the degree of temporal protrusion showed a marked decrease in the mean difference at a 95% confidence interval. The results were acceptable.Conclusions In the treatment of sagittal fractures at the temporal root of the zygomatic arch, it is acceptable to use indirect reduction and non-fixation methods. This leads to a satisfactory aesthetic and functional outcome.
Keywords: Zygomatic fractures; Facial asymmetry; Follow-up studies